The role of the two-hidrocarbon agencies in achieving environmental security within the framework of sustainable development in the light of law N° 19-13 - Kharchi, Ilham (Milev Journal of Research and Studies, 2022)
This study aims to show the importance of the role played by the independent régulatory authorities in achieving environmental security within the framework of sustainable development by evaluating the importance and strength of the powers granted to them in this framework. The study reached the following conclusions: The legislator did not reach the granting of strong and important powers in the field of environmental protection, given that the issues related to the latter remain in the hands of the traditional administrative authorities, and even the punitive competence targets the field of regulating of the sector and not protecting the environment.